ANP32B Deficiency Protects Mice From Lethal Influenza A Virus Challenge by Dampening the Host Immune Response - Beck, Sebastian; Zickler, Martin; Pinho dos Reis, Vinícius; Günther, Thomas; Grundhoff, Adam; Reilly, Patrick T.; Mak, Tak W.; Stanelle-Bertram, Stephanie; Gabriel, Gülşah (Frontiers in Immunology, 2020)
Deciphering complex virus-host interactions is crucial for pandemic preparedness. In this study, we assessed the impact of recently postulated cellular factors ANP32A and ANP32B of influenza A virus (IAV) species specificity on viral pathogenesis in a genetically modified mouse model. Infection of ANP32A-/- and ANP32A+/+ mice with a seasonal H3N2 IAV or a highly pathogenic H5N1 human isolate did not result in any significant differences in virus tropism, innate immune response or disease outcome. However, infection of ANP32B-/- mice with H3N2 or H5N1 IAV revealed significantly reduced virus loads, inflammatory cytokine response and reduced pathogenicity compared to ANP32B+/+ mice. Genome-wide transcriptome analyses in ANP32B+/+ and ANP32B-/- mice further uncovered novel immune-regulatory pathways that correlate with reduced pathogenicity in the absence of ANP32B. These data show that ANP32B but not ANP32A promotes IAV pathogenesis in mice. Moreover, ANP32B might possess a yet unknown immune-modulatory function during IAV infection. Targeting ANP32B or its regulated pathways might therefore pose a new strategy to combat severe influenza.